2008
DOI: 10.1038/ismej.2008.50
|View full text |Cite
|
Sign up to set email alerts
|

High aromatic ring-cleavage diversity in birch rhizosphere: PAH treatment-specific changes of I.E.3 group extradiol dioxygenases and 16S rRNA bacterial communities in soil

Abstract: Genes encoding key enzymes of catabolic pathways can be targeted by DNA fingerprinting to explore genetic degradation potential in pristine and polluted soils. We performed a greenhouse microcosm experiment to elucidate structural and functional bacterial diversity in polyaromatic hydrocarbon (PAH)-polluted soil and to test the suitability of birch (Betula pendula) for remediation. Degradation of PAHs was analysed by high-performance liquid chromatography, DNA isolated from soil amplified and fingerprinted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 72 publications
4
53
0
Order By: Relevance
“…For instance, bacteria appeared to be generally stimulated in contaminated soils along with many functions, whereas fungi were more clearly stimulated in non-contaminated soils. Similarly, the rhizosphere effect of birch on soil microbial communities was reported to depend on PAH concentration (Sipilä et al, 2008). One possible explanation for this result is that plants recruit the rhizosphere microbial communities from the adjacent bulk soil (de Ridder-Duine et al, 2005;Dennis et al, 2010;Lundberg et al, 2012), and that contaminated and non-contaminated soils harbored different starting microbial communities (Figure 4).…”
Section: Metatranscriptomics Of the Rhizospherementioning
confidence: 92%
“…For instance, bacteria appeared to be generally stimulated in contaminated soils along with many functions, whereas fungi were more clearly stimulated in non-contaminated soils. Similarly, the rhizosphere effect of birch on soil microbial communities was reported to depend on PAH concentration (Sipilä et al, 2008). One possible explanation for this result is that plants recruit the rhizosphere microbial communities from the adjacent bulk soil (de Ridder-Duine et al, 2005;Dennis et al, 2010;Lundberg et al, 2012), and that contaminated and non-contaminated soils harbored different starting microbial communities (Figure 4).…”
Section: Metatranscriptomics Of the Rhizospherementioning
confidence: 92%
“…Specific information on the potential of biodegradation can be obtained by examining functional genes encoding enzymes involved in degradation pathways (Smith andOsborn, 2008 andBombach et al, 2010). For example, in the case of diuron, Pesce et al (2013) recently demonstrated that diuron mineralization kinetics obtained with soil samples were correlated to diuron-degrading genetic potentials estimated from the quantification of the abundance of the phenlylurea hydrolase gene puhB, confirming that degradation genes could be potential biomarkers for the detection of organic xenobiotics (Sipilä et al, 2008). In addition, Monard et al (2013) recently showed that atrazine mineralizing ability of different soils was correlated to the expression level of atzD gene, coding for an enzyme responsible for s-triazine ring opening.…”
Section: Did the Ban Of Diuron Lead To A Decrease In The Exposure Levmentioning
confidence: 99%
“…These wholecommunity fingerprinting approaches have been used recently successfully to study complex bacterial communities, to estimate the diversity and relative abundance of individual bacterial species within detectable bacterial communities (Hewson and Fuhrman 2004;Fedi et al 2005;Sipilä et al 2008;Iannelli et al 2012;Vajna et al 2012). In addition, using traditional selective cultivation dependent microbiological methods we are able to isolate site specific hydrocarbonoclastic bacterial strains which could form the basis of a new bacterial inoculant for bioremediation purposes.…”
Section: Introductionmentioning
confidence: 99%